PELATIHAN PEMANFAATAN KONTEN RELIGI BAGI REMAJA MASJID AL JIHAD UNTUK MENDUKUNG PERUBAHAN PERILAKU ISLAMI - Lutfhi, Muhammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Social media is one of the many results of today's technological sophistication. Social media is now present to provide an easy and efficient interaction service. This situation continues to encourage programmers to continue to develop the capabilities of the applications they make for the convenience of their users, but without realizing this sophistication can damage the morals of adolescents when their use is not appropriate, it can damage one's behavior. The purpose of this community service is to provide content utilization training to mosque youth to support changes in Islamic behavior. The methods used in this activity are participatory method, implementation method, and approach method. The result of this activity is that the utilization of religious content on social media in increasing the Islamic behavior of Al Jihad Mosque Teenagers can be understood by the participants, because they realize that to understand and learn Islam in particular, it can be easily accessed by content, such as Islamic video content in the form of Islamic lecture videos on social media.